Shared bacterial communities between soil, stored drinking water, and hands in rural Bangladeshi households - Fuhrmeister, E.R. (2021)
Understanding household-level transmission pathways of fecal pathogens can provide insight for developing effective strategies to reduce diarrheal illness in low- and middle-income countries. We applied whole bacterial community analysis to investigate pathways of bacterial transmission in 50 rural Bangladeshi households. SourceTracker was used to quantify the shared microbial community in household reservoirs (stored drinking water, soil, and hands) and estimate the percentage of fecal-associated bacteria from child and mothers’ feces in these reservoirs. Among the reservoirs studied, most bacterial transfer occurred between mothers’ and children’s hands and between mothers’ hands and stored water. The relative percentage of human fecal-associated bacteria in all household reservoirs was low. We also quantified the number of identical amplicon sequence variants within and between individual households to assess bacterial community exchange in the domestic environment. Intra-household sharing of bacteria between mothers’ and children’s hands and between hands and soil was significantly greater than inter-household sharing.